Defective kinetics of cytochrome c oxidase and alteration of mitochondrial membrane potential in fibroblasts and cytoplasmic hybrid cells with the mutation for myoclonus epilepsy with ragged-red fibres ('MERRF') at position 8344 nt - Antonická, H; Floryk, D; Klement, P; Stratilová, L; Hermanská, J; Houstková, H; Kalous, M; Drahota, Z; Zeman, J; Houstek, J (The Biochemical journal, 1999)
We have investigated pathogenic effects of the tRNA(Lys) A8344G mutation associated with the syndrome myoclonus epilepsy with ragged-red fibres (MERRF) by using fibroblasts and fibroblast-derived cytoplasmic hybrid cells harbouring different percentages of mutated mitochondrial DNA (mtDNA). The activity of cytochrome c oxidase (COX) in patient fibroblasts with 89% mutated mtDNA was decreased to 20% of the control levels. COX exhibited altered kinetics, with a decreased V(max) for both the low-affinity and high-affinity phases; however, the K(m) values were not significantly changed. The substrate-dependent synthesis of ATP was decreased to 50% of the control. Analysis of the mitochondrial membrane potential, DeltaPsi, in digitonin-treated cells with tetramethylrhodamine methyl ester (TMRM) with the use of flow cytometry showed a 80% decrease in DeltaPsi at state 4 and an increased sensitivity of DeltaPsi to an uncoupler in fibroblasts from the patient. The investigation of transmitochondrial cytoplasmic hybrid clones derived from the patient's fibroblasts enabled us to characterize the relationship between heteroplasmy of the MERRF mutation, COX activity and DeltaPsi. Within the range of 87-73% mutated mtDNA, COX activity was decreased to 5-35% and DeltaPsi was decreased to 6-78%. These results demonstrate that the MERRF mutation affects COX activity and DeltaPsi in different proportions with regard to mutation heteroplasmy and indicate that the biochemical manifestation of the MERRF mutation exerts a very steep threshold of DeltaPsi inhibition.
Keywords: intracelulární membrány; mutace; Intracellular Membranes; Kinetics; membránové potenciály; Electron Transport Complex IV; průtoková cytometrie; Fibroblasts; Oxidative Phosphorylation; lidé; respirační komplex IV; Flow Cytometry; Mutation; adenosintrifosfát; fibroblasty; fluorescenční spektrometrie; separace buněk; oxidativní fosforylace; Adenosine Triphosphate; Cell Separation; MERRF Syndrome; Spectrometry, Fluorescence; kinetika; syndrom MERRF; Membrane Potentials; Humans